A organização pedológica em Guiricema/MG, no alto vale do Rio Paraíba do Sul, e sua relação com os diferentes patamares geomorfológicos do sudeste de Minas Gerais - Malena Silva Nunes (2020)
The analysis of the pedological cover allows the understanding of soils from their lateral distribution, revealing aspects of their transformation and their intimate relationship with the relief. Studies in the staggered plateaus of southeastern Minas Gerais point to geomorphological Evolution from the lowest base level on one side of the escarpment, considering the rework of the relief with retreta of the escarpments and expansion of the depressed área. This work investigated the pedological transformations in a slope in the river basin of the river Paraíba do Sul. The methodological procedures involved bibliographic surveys, production of cartographic material, field work and laboratory analysis. The methodology of the Structural Analysis of Pedological Cover (Boulet et al., 1982 a, b. c) was applied, and samples were collected for physical, chemical, mineralogical analysis and for making thin sheets for micromorphological analysis, from seven soil profiles, aligned in toposequence. The pedological cover showed a high degree of Evolution in view of the negative ∆pH values of the disgnostic horizons and the predominance of kaolinite and oxides along the slope. The migration of the clay is already in the morphological description of the profiles, with a waxy slope at the foot of the slope. By granulometric analysis, there is a greater presence os sand in the superficial horizons and clay in the diagnostic horizons, in addition to the textural gradiente in the medium slope. The silt/clay rationship decreases with depth, showing an increase in clay concentration due to vertical and lateral migration. It should be noted that the processes associated with the movement of the clay are favored, among others, by the topography of the slope (the presence of concavities) and by the higher ADA values in the superficial horizons. In the micromorphological analysis, the occurrence of nodules contributed to the definition of Oxisols. And the presence of these in the BC horizon of the Argisol (P3) was understood as pedological relics of previous Oxisols characteristics, as well as the presence of the Bt horizon superimposed to the Bw in the Argisol (P4) indicated a pedological transformation with a possible substitution of the oxisolic to argisolic profile, resulting in the suggestion of classification of the profile as ARGISOL YELLOW Dystrophic latossolic. The abundant plasma concentrations from the upper slope, including the occurrence of textural coatings, reaffirmed the vertical and lateral movement of the clay. The identification of pedological features of textural cladding in the Cambisol at the lower slope defined an argisolic aspect. The pedological cover is distinguished, therefore, according to the topographic differentiations that determine the surface and subsurface water behavior. At the top and shoulder of the slope, flat and convex áreas, are the Oxisols. The increase in slope, associated with the presence of concavities, promotes an increase in surface runoff and the presence of a Bt horizon, showing the accumulation of clay. Thus, it appears that morphological changes in the landscape, with the expansion of the depression and the retreta of the escarpments, resulted in two fronts of pedological transformation, one composed by the Oxisol-Argisol transformation system (from top to medium slope), and another by the Cambisol-Argisol system (at the lower). The deepening of this study and the performance of other analyzes will allow a better understanding of the transformation systems and their relationship with the regional geomorphological evolution.